CONTENT ANALYSIS OF FURNITURE PRODUCT PROMOTION WITH ENVIRONMENTAL CLAIMS ON INSTAGRAM - Carissa Fauzia Arimurti; Ujang Sumarwan (Journal of Child, Family, and Consumer Studies, 2023)
Increasing public awareness about the environment has pushed companies to apply the green concept and claim their products as environmentally friendly, such as furniture products. This study analyzes product characteristics, promotional posts, and characteristics of claims in furniture product promotion uploads with green claims on Instagram and its fulfillment of the Law of Consumer Protection. The study analyzed 200 promotional uploads of furniture products with green claims on Instagram. The data was processed descriptively using IBM SPSS Statistics 25.0 and Voyant Tools. The results indicate that the uploads contain the most elements of environmentally friendly materials (78%), are subjective (60,5%), product-oriented (85,5%), and are categorized as ambiguous (65%). Furthermore, analysis of the Consumer Protection Law (UUPK) shows that article 9 has the most (59,5%) violated by business actors. Therefore, it requires cooperation between consumers, business actors, and the government to reduce the spread of deceptive green claims on furniture product promotions.